Anatomy and Variants of Hepatic Arteries in 120 Patients Studied with 128 Slice Volumetric Scan in Nepalese Population (Nepalese Journal of Radiology, 2022)
Introduction: Modern advances in radiology, imaging, and novel surgical methods have greatly aided doctors in making both surgical and non-surgical decisions. During surgery, anatomical variances are frequently encountered by surgeons, making operation complex and occasionally challenging. The purpose of our study was to evaluate the hepatic artery and its variants, including the length and diameter of the right and left hepatic arteries. This information is vital for patients undergoing major hepatic surgeries and hepatic transplantationMethods: A total of 120 patients who underwent contrast-enhanced Triphasic CT of the abdomen were evaluated with the consent of the ethics committee at Chitwan medical college. Study subjects were selected on a random basis, who had no previous abdominal or hepatic surgeries, and without the known hepatic disease.Results: Out of 120 participants, 63 (52.5%) were male and the rest 57(47.5 %) were females. Normal anatomy was observed in 104 cases (86.7%) and the rest of the 16 cases showed an anomalous hepatic arterial pattern, which consisted of Michel’s type III in 6 cases (5%), Type IV in 1 case (0.8%) and Type X in 3 cases (2.5%); and 5 cases (4.2%). did not fall under Michel’s Classification. Supply to segment IV of the liver was observed from Left hepatic artery in 97 cases (80.8%) and from the right hepatic artery in 23 cases (19.2%).Conclusions: Many hepatic arterial variants which did not fall under Michel’s classification were observed in our population.